Pendayagunaan Sampah Organik Dapur Menjadi Eko Enzim Cairan Multiguna - asmawati, Asmawati; Jafar, Faisal; Sabaruddin, Sabaruddin; Hambali, Amriani; Inderiati, Sitti; Chadijah, St. (JatiRenov: Jurnal Aplikasi Teknologi Rekayasa dan Inovasi, 2025)
Kitchens are the highest source and continuously produce organic waste, therefore it is necessary to manage the waste in order to reduce the bad impact caused. This activity was carried out in the form of counseling, using the lecture-feedback method with power point slide media, followed by a demonstration and practices on how to make eco-enzymes. Participants were given counseling on the impact of garbage piles that are thrown in any place, the impact of burned waste, and how to manage organic waste produced from the kitchen into useful products to help preserve the environment. The results of the service showed that this activity had been able to increase the knowledge and skills of farmers and women farmers in Manggalung Village, Mandalle District in processing kitchen organic waste into a multi-benefit product. This is shown by the number of participants who attended, the response, enthusiasm, and good participation during the activity, as well as the results of the practices of making and applied the eco-enzymes at their respective homes and planting areas. The quality of the eco-enzyme produced had met the standard with indicators such as brownish color, fresh sour smell, pH 3.4 and no maggots. The results of this community service activity are very important because the target group can already manage and utilize waste into something valuable.